The relationship between enterprise human capital structure and international M&A performance based on cultural differences in China - Ye Liu; Fang-yuan Zhao; Si-qi Jia; Li-rong Qiu (PLoS ONE, 2025)
With the rapid development of China’s economy, increasing Chinese companies have acquired international technology resources, improved production efficiency, opened up international markets through international mergers and acquisitions, and realized the expansion of enterprises in the global capitalist market. Especially in recent years, the rapid development of international mergers and acquisitions of Chinese enterprises, as well as the increasingly frequent activity in the international market, makes the performance of international mergers and acquisitions become the focus of attention of enterprises, and also increasingly become a focus of scholars. Although the human capital structure of enterprises as an internal factor of enterprises has been studied by most scholars. However, in the existing literature, more studies focus on the impact of corporate human capital structure on corporate performance, while the impact of human capital on international M&A performance is not sufficient. The performance of international mergers and acquisitions is relatively a more complex factor, which is influenced by more factors and has higher research value. Based on the performance of international mergers and acquisitions, this paper explores how the human capital structure of enterprises can play a role in improving the competitiveness of enterprises under the background of economic globalization, so as to provide reference for enterprises to gain competitive advantage in the international market. This study selects Chinese listed companies with international mergers and acquisitions from 2008 to 2015 as research samples, and empirically analyzed the relationship between corporate human capital structure and international M&A performance. The four conclusions obtained are as follows: (1) Employee compensation, employee education level and employee technical personnel ratio are significantly positively correlated with the company’s international M&A performance; (2) Enterprise training in both short-term and long-term. Neither of them has a important impact on the company’s international M&A performance; (3) Employee turnover has a critical negative impact on the company’s international M&A performance; (4) After introducing cultural differences as a regulatory variable, it is found that cultural differences can weaken the impact of human capital factors on the performance of international M&A. Finally, this paper puts forward suggestions on how to better utilize the human capital advantages of the company in the global economic background with the intention of improving the performance of international M&A.